The Effect of Multimodal Digital English Book for Self-Learning in Elementary School - Khosiyono, Banun Havifah Cahyo; Sulaimon, Jamiu Temitope (JADEs Journal of Academia in English Education, 2024)
The use of multimodal digital teaching methods for English has grown significantly. A small number of researchers, meanwhile, have looked at how elementary school students feel learning to tell stories in digital form using English as a second language. To bridge the gap, this study reports the effect of Digital Story Telling for Self-Learning of English in Elementary School. This research method uses experimental design using a control and experimental group. The research participants are 40 third-grade students from two elementary schools in Indonesia using random sampling technique. The results show that there is a significant influence of the use of multimodal digital English books with self-learning to learn English. According to the study, elementary school students can improve their self-learning and learn English by participating in multimodal digital English book.